Serial measurement of interleukin‐6 and risk of mortality in anticoagulated patients with atrial fibrillation: Insights from ARISTOTLE and RE‐LY trials. (1st August 2020) - Aulin, Julia; Hijazi, Ziad; Siegbahn, Agneta; Andersson, Ulrika; Alexander, John H.; Connolly, Stuart J.; Ezekowitz, Michael D.; Gersh, Bernard J.; Granger, Christopher B.; Horowitz, John; Hylek, Elaine M.; Lopes, Renato D.; et al.
Abstract: Background: The inflammatory biomarker interleukin‐6 (IL‐6) is associated with mortality in atrial fibrillation (AF). Objective: To investigate if repeated IL‐6 measurements improve the prognostication for stroke or systemic embolism, major bleeding, and mortality in anticoagulated patients with AF. Methods: IL‐6 levels by ELISA were measured at study entry and at 2 months in 4830 patients in the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE) trial with 1.8 years median follow‐up. In the Randomized Evaluation of Long‐Term Anticoagulation Therapy (RE‐LY) trial, IL‐6 was measured at study entry, 3, 6, and 12 months in 2559 patients with 2.0 years median follow‐up. Associations between a second IL‐6 measurement and outcomes, adjusted for baseline IL‐6, clinical variables, and other cardiovascular biomarkers, were analyzed by Cox regression. Results: Median IL‐6 levels were 2.0 ng/L (interquartile range [IQR] 1.30‐3.20) and 2.10 ng/L (IQR 1.40‐3.40) at the two time‐points in ARISTOTLE, and, in RE‐LY, 2.5 ng/L (IQR 1.6‐4.3), 2.5 ng/L (IQR 1.6‐4.2), 2.4 ng/L (IQR 1.6, 3.9), and 2.4 ng/L (IQR 1.5, 3.9), respectively. IL‐6 was associated with mortality; hazard ratios per 50% higher IL‐6 at 2 or 3 months, respectively, were 1.32 (95% confidence interval, 1.23‐1.41; P  < .0001) in ARISTOTLE, and 1.11 (1.01‐1.22, P  = .0290) in RE‐LY; with improved C index from 0.74 to 0.76 in ARISTOTLE, but not in the smaller RE‐LY cohort. There were no consistent associations with second IL‐6 and stroke or systemic embolism, or major bleeding. Conclusions: Persistent systemic inflammatory activity, assessed by repeated IL‐6 measurements, is associated with mortality independent of established clinical risk factors and other strong cardiovascular biomarkers in anticoagulated patients with AF.